Interrelatedness between Organizational Culture and Human Resource Management in the Context of Corporate Entrepreneurship - Syafri Naldi; Dapit Alexsander; Margo Purnomo (Bina Nusantara University, 2021)
There has been numerous research on corporate entrepreneurship typically referring to organizational culture or human resource management (HRM). The research aimed to complement previous research that had explored the link between entrepreneurship, the culture of organization, and HRM. The purpose of the research was to explain the operationalization of the three principles and to elaborate the interrelationship between them in the context of corporate entrepreneurship. The research used a systematic review process, namely an indepth literature review of results from 25 articles based on certain keywords and limitations. The result produces a model that describes the influence of HRM on organizational culture, which is expected to inspire businesses to adopt an approach to corporate entrepreneurship and enhance the efficiency of the company. Future research is suggested to have more than one database and use more research article sources published in over 10-20 years. It is expected that future research come up with extended range of observations and results on how science has progressed.